1987
DOI: 10.1001/jama.1987.03390140082031
|View full text |Cite
|
Sign up to set email alerts
|

Do Families Get Family Care?

Abstract: To determine the prevalence of family care, we measured the extent to which a subset of 732 families, from those enrolled in the Rand Health Insurance Experiment, perceive and use a single primary care physician. Although only 16.7% of these families had all members with a majority of their visits to the same physician, 45.4% identified a single primary care physician for all family members. (For older couples, this percentage reached 73.5%). An intermediate proportion of families had visits by all family memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Yet study after study has suggested that, at most, only 25-30% of families in the U.S. meet this simple criterion. A representative study was one from the Division of Family Medicine at UCLA (1) in which data from a sample of 732 families enrolled in the Rand Health Insurance Experiment were examined. In only 16.7% of these families did family members have a majority of their medical visits to the same physician (a reasonable index of whether they were using the same primary care physician).…”
Section: Why We Need a Family Therapy Perspectivementioning
confidence: 99%
“…Yet study after study has suggested that, at most, only 25-30% of families in the U.S. meet this simple criterion. A representative study was one from the Division of Family Medicine at UCLA (1) in which data from a sample of 732 families enrolled in the Rand Health Insurance Experiment were examined. In only 16.7% of these families did family members have a majority of their medical visits to the same physician (a reasonable index of whether they were using the same primary care physician).…”
Section: Why We Need a Family Therapy Perspectivementioning
confidence: 99%